Simulation of optical communication systems using MATLAB - Chew, Kheng Heng. (2008)
In this project, a simulation software using MATLAB was developed. A number of new system features were developed. These include a pseudo-random step function bit pattern as input signal (which was generated and superimposed on a DC bias current to drive the laser), On-Off Keying (OOK) modulation; optical filter for optical signal filtering; the photo-detector and receiver pulse-shaping filter for recovering the OOK signal to electrical current for evaluating the systems performance. Directly modulated semiconductor laser through carrier injection not only induces dispersion in long haul single-mode fiber communication systems, but also causes energy loss and signal distortion when frequency selective elements such as filter is present.